Keberhasilan Progam Pengembangan Usaha Agribisnis Perdesaan (Puap) Di Kecamatan Sungai Kunyit Kabupaten Mempawah (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
This study aimed to analyze the influence of the entrepreneurial spirit of farmer group caretaker to the success of rural agribusiness development program. The analysis used in this research is multiple linear regression analysis. This study uses 36 board of farmer group in Sei Kunyit, Mempawah District. The results showed that entrepreneurship has a positive and significant value to the success of the rural agribusiness development program. While the application of management has a negative value and not significant to the success of rural agribusiness development program in Sei Kunyit, Mempawah District. Attribute entrepreneurship provides the effect of 0.261. This sshows that for the success of rural agribusiness development programs to consider and foster the entrepreneurial spirit of farmer group caretaker.Keywords : Entrepreneurial Spirit, Applicaton of Busness Magement, Success of Rural Agrbusiness Development Effort